New proposals for regional integration: trends and transformation challenges (2020)
This book addresses the challenges generated by the new international and regional trends, which have arisen from the transformations of the current international system as a result of the most recent events. The authors start, as a frame of reference, from a changing international scenario, from which they analyze and reflect on exhaustion and stagnation, crisis or chaos, the growing uncertainty of Latin American integration processes and projects. Among the recent national, regional and international changes, the relative weight loss of the West, the relative withdrawal of the United States as a paymaster, the consolidation of new emerging powers, the new strategies of international insertion such as interregionalism and the effects of the globalization that, in the face of negative externalities, demands greater international cooperation for collective action. Opportunity scenarios are identified and highlighted to overcome the crossroads of the current state in terms of regional integration.